Gradient Bandgap‐Tunable Perovskite Microwire Arrays toward Flexible Color‐Cognitive Devices. (2nd January 2023) - Fu, Yue; Yuan, Meng; Zhao, Yingjie; Dong, Meiqiu; Guo, Yangwu; Wang, Kui; Jin, Chunqi; Feng, Jiangang; Wu, Yuchen; Jiang, Lei
Abstract: Color‐cognitive detection plays an important role in many developing applications such as optical sensing, high‐solution imaging, wearable biometric monitoring, and human visual cognitive system. Although color‐cognitive devices have been demonstrated, the large size, complex manufacturing, high cost, and non‐flexible processing impede their applications for distinguishing color information. Herein, gradient bandgap‐tunable perovskite microwire arrays with excellent crystallinity and pure crystallographic orientation are realized by the synergy of the capillary‐bridge assembly method and mild component engineering processing, yielding high‐performance integrated color‐cognitive devices with the spectral resolution of 14 nm ranging from 405 nm to 760 nm, responsivities over 10 3 A W −1, and detectivities over 10 15 Jones. Furthermore, the integrated flexible color‐cognitive devices are demonstrated for accurately recognizing similar colors, which can be applied in color blindness correction. The efficient color recognition performances, together with the flexible processing, open new opportunities for the on‐chip integration of wearable devices based on microwire arrays. Abstract : Gradient bandgap‐tunable perovskite microwire arrays are fabricated by the synergy of component engineering and capillary‐bridge assembly technique. Based on single crystallinity and pure crystallographic orientation of microwire arrays, on‐chip integrated flexible color‐cognitive devices are demonstrated with a spectral resolution of 14 nm (405–760 nm), responsivities over 10 3 A W −1, and detectivities over 10 15 Jones.